2014
DOI: 10.4103/0257-7941.147433
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Macrotyloma uniflorum seed on bile lithogenicity against diet induced cholelithiasis on mice

Abstract: Background:The seeds of Macrotyloma uniflorum Lam. (Family Fabaceae) contain extractable total and tannins with reported hepatoprotective, hypocholesterolemic and antioxidant activity. In this study, dietary M. uniflorum seed, methanolic and acetone extracts (ME and AE) were examined for their bile-antilithogenic potential.Materials and Methods:Mice fed with 1% cholesterol and 0.5% cholic acid lithogenic (LG) diet for 8 weeks resulted in cholesterol super saturation in gallbladder bile, which promotes the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…The aqueous extract group showed the lowest incidence of CGS (60.21%) and also significant (P<0.01) reduction of gall bladder weight at 300 mg/kg than the methanolic extract, i.e. 60.0% 48 .…”
Section: Anti-allergic or Anti-anaphylactic Activitymentioning
confidence: 82%
See 1 more Smart Citation
“…The aqueous extract group showed the lowest incidence of CGS (60.21%) and also significant (P<0.01) reduction of gall bladder weight at 300 mg/kg than the methanolic extract, i.e. 60.0% 48 .…”
Section: Anti-allergic or Anti-anaphylactic Activitymentioning
confidence: 82%
“…Anticholelithiatic Activity: The methanolic and aqueous extracts were prepared from seeds of horse gram and were examined for their bile antilithogenic potential on mice 48 . The methanolic and aqueous extracts were used for the presence of phenolics, tannins, and flavonoids.…”
Section: Anti-allergic or Anti-anaphylactic Activitymentioning
confidence: 99%
“…13 It was also found in previous research studies that some plants containing magnesium exhibit anticholilithiatic effect. 24 Thus the presence of magnesium may be the reason behind the anticholilithiatic activity of apricot as it is rich in magnesium. 13…”
Section: Discussionmentioning
confidence: 99%
“…Gall stone formation is a complicated and multi factorial process. It is associated with various metabolic and genetic factors such as aging, gall bladder hypomotility, and imbalance in nucleating and antinucleating factors, cholecystokinin (CCK) deficiency and mutation in Lith gene [24]. Studies have shown that cholesterol and cholic acid produce cholesterol gallstone disease [25].…”
Section: Discussionmentioning
confidence: 99%